2021
DOI: 10.14814/phy2.14739
|View full text |Cite
|
Sign up to set email alerts
|

The effect of L‐arginine supplementation on maximal oxygen uptake: A systematic review and meta‐analysis

Abstract: Background The efficacy and safety of L‐arginine supplements and their effect on maximal oxygen uptake (VO2 max) remained unclear. This systematic review aimed to investigate the effect of L‐arginine supplementation (LAS) on VO2 max in healthy people. Methods We searched PubMed, Scopus, Web of Science, Cochrane, Embase, ProQuest, and Ovid to identify all relevant literature investigating the effect of LAS on VO2 max. This meta‐analysis was conducted via a random‐effects model for the best estimation of desired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
2
6
0
1
Order By: Relevance
“…This observation suggests that redox balance in a cell has a positive effect on the abovementioned molecular pathways, potentially indicating a regulatory role of redox balance in various cellular and metabolic pathways. VO2max was correlated with L-arginine biosynthesis in males, which fits well with the result of the study which reported increased VO2max after L-arginine supplementation (Rezaei et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…This observation suggests that redox balance in a cell has a positive effect on the abovementioned molecular pathways, potentially indicating a regulatory role of redox balance in various cellular and metabolic pathways. VO2max was correlated with L-arginine biosynthesis in males, which fits well with the result of the study which reported increased VO2max after L-arginine supplementation (Rezaei et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Arginine, which is present in Maca, affects endurance and heart (25). Rezaei et al reported that meta-analysis indicated that supplementation with arginine could increase VO2 max in healthy people (26). Speer et al also support the fact that the combination of arginine and citrulline might increase nitric oxide production and enhance vasodilation, thereby improving athletes' performance (27).…”
Section: Discussionmentioning
confidence: 99%
“…8 f). l -Arg plays a positive regulatory role in the bioavailability of nitric oxide, which is beneficial for improving coronary perfusion and cardio-pulmonary function 33 . During strenuous exercise, l -Arg up-regulated the utilization of glucose and lipid through PI3K/Akt signal pathway and mediate myocardial oxidative stress by cleaning ROS and enhancing antioxidant enzymes activity 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%